INDEKS KOMPOSIT PEKERJAAN TIDAK LAYAK (IPTL) DI INDONESIA - Katamso Noto Santoso; Hardius Usman (Research Centre for Population, Indonesian Institute of Sciences, 2020)
The open unemployment rate in Indonesia was 5.50 in August 2017. This figure was the lowest level in comparison to rates in previous years. The declining rate of unemployment over the past decade was in line with the increasing trend of risky work. This situation may indicate recent job opportunities are likely to be risky or categorized as non-decent works. To understand the conditions of non-decent work in Indonesia, a composite index measurement, which is currently not available, is needed. Thus, this study aims to develop such a composite index called Non-Decent Work Index (NDWI) to fill this gap. The method applied for the composite index formation is factor analysis. The findings indicate three factors of NDWI. It is also found that NDWI has a significant relationship with human development index and labor productivity. Therefore, Indonesia government needs to address the problem of inadequate employment conditions in this country. It is because decent work is the central aspect of efforts to reduce poverty